Moderately halophlic bacteria isolated from Atacocha salt brine in Ayacucho - Femández Jerí, Yadira (2007)
Halophilic bacteria produce a great variety of substances and enzymes with interesting biotechnological applications. In order to isolate moderately halophilic bacteria from saline environments in Atacocha (Ayacucho}, salt samples were collected and inoculated in saline medium (5% total salts) with 0.5% yeast extract. After one week incubation they were streaked onto agar plates prepared with the same saline medium as before but solidified with 2% agar. Ten, out of 40 isolates, were selected based on their differential cultural and morphological features. Further characterization of the selected isolated included tolerance to NaCl, temperature and pH ranges for growth and some biochemical and nutritional tests. The strains tolerated 0.1 to 4.0 M NaCl and had their optima between 1.5 and 2.0 M, the temperatures and pH values enabling growth were 4 to 37 ºC and 5 to 9, respectively. The moderately halophilic bacteria isolated showed phenotypic features similar to those of the species of the genera Halomonas and Chromohalobacter.